2001
DOI: 10.1046/j.1365-2958.2001.02298.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of RsrA, a zinc‐binding anti‐sigma factor with a thiol–disulphide redox switch

Abstract: SummaryIn the Gram-positive bacterium, Streptomyces coelicolor A3(2), expression of the thioredoxin system is modulated by a sigma factor called s R in response to changes in the cytoplasmic thiol±disulphide status, and the activity of s R is controlled post-translationally by an anti-sigma factor, RsrA. In vitro, the antisigma factor activity of RsrA, which contains seven cysteines, correlates with its thiol±disulphide redox status. Here, we investigate the function of RsrA in vivo. A constructed rsrA null mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
180
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(188 citation statements)
references
References 55 publications
6
180
0
2
Order By: Relevance
“…The arrangement of genes at the M. tuberculosis sigH locus resembles that of the Streptomyces coelicolor A3(2) sigR locus (38,39), and it has been shown that the gene adjacent to sigR (rsrA) inhibits SigR activity by functioning as SigR-sequestering anti-factor (40). Because MT3318 transcriptional levels parallel those of sigH, it appears likely that the SigH and the MT3318 gene product are produced in equimolar quantities.…”
Section: Construction Of the Sigh Mutant And Complemented Strainmentioning
confidence: 99%
“…The arrangement of genes at the M. tuberculosis sigH locus resembles that of the Streptomyces coelicolor A3(2) sigR locus (38,39), and it has been shown that the gene adjacent to sigR (rsrA) inhibits SigR activity by functioning as SigR-sequestering anti-factor (40). Because MT3318 transcriptional levels parallel those of sigH, it appears likely that the SigH and the MT3318 gene product are produced in equimolar quantities.…”
Section: Construction Of the Sigh Mutant And Complemented Strainmentioning
confidence: 99%
“…Oxidation of RsrA leads to the formation of disulphide bonds and the concomitant release of Zn(II). Thus, it is likely that the role of RsrA as a sensor of oxidative stress involves one or more reactive cysteine residues co-ordinated to Zn(II) (Paget et al, 2001b). A. OxyR is a tetrameric DNA-binding protein that can be reversibly oxidized to form a disulphide linking Cys-199 and Cys-208 (E. coli numbering).…”
Section: Introductionmentioning
confidence: 99%
“…In S. coelicolor, the activity of s R is regulated by anti-s factor RsrA, which is inactivated by formation of disulphide bonds and releases s R to transcribe its regulon under oxidative stress (Bae et al, 2004;Kang et al, 1999;Paget et al, 2001a, b). An unstable larger isoform of s R with a 55 aa N-terminal extension is induced by diamide treatment; this extension is transcribed from the s R -dependent promoter and translated from an upstream start codon (Kim et al, 2009).…”
Section: Discussionmentioning
confidence: 99%